Transmission Pipeline Planning from Kregan Water Treatment Plant to Watu Gadjah Tank by PERUMDA PDAM Sleman Using EPANET 2.2 - Dewata, Hendra; Faishal, Faris Amir; Marleni, Ni Nyoman Nepi (Universitas Negeri Yogyakarta, 2024)
Clean water is vital as it directly impacts health and influences various aspects of life, including social, economic, and cultural activities. To address the clean water supply requirements in the area, PERUMDA PDAM Sleman, Yogyakarta, is currently planning for a transmission network linking the Kregan WTP to the Watu Gadjah Tank. The pipeline planning is carried out to ensure efficient and optimal network performance. The pipeline planning use both primary and secondary data. The primary data was obtained from surveys, while the secondary data was obtained though previous research and planning, regulation, and from the other sources. The pipeline network analysis carried out using EPANET 2.2. software. EPTANET was selected because of its cost-effectiveness and robust capabilities in modeling drinking water networks, with the advantage of being re-programmable. The results of the analysis are then adjusted to the planning standards that applicable in Indonesia. Risk analysis was carried out based on experience and expert opinion. The results of the planning showed that the maximum pressure on the transmission network was 84.21m on Pendowo Road. The velocity between 1.03 m/s and 1.63 m/ss with the highest headloss was 10.33 m/km. Based on the results of the planning, the entire parameter meets the standard of the applicable planning criteria. The results of the analysis indicate that the technical specifications of the pipe used must be able to withstand a pressure of 92,63m. There was a potential risk that network performance may be disrupted both in terms of network performance, implementation of development, and operational stages. The re-examination and the development of operational standard procedures is needed to ensure that planning has been in line with the expectations, can be implemented, and can be operated efficiently.